Mechanisms of Mononuclear Phagocyte Recruitment in Alzheimer's Disease - Hickman, Suzanne E.; Khoury, Joseph El (CNS & Neurological Disorders - Drug Targets, 2010)
Alzheimer's disease (AD) is associated with a significant neuroinflammatory component. Mononuclear phagocytes including monocytes and microglia are the principal cells involved, and they accumulate at perivascular sites of β-amyloid (Aβ) deposition and in senile plaques. Recent evidence suggests that mononuclear phagocyte accumulation in the AD brain is dependent on chemokines. CCL2, a major monocyte chemokine, is upregulated in the AD brain. Interaction of CCL2 with its receptor CCR2 regulates mononuclear phagocyte accumulation in a mouse model of AD. CCR2 deficiency leads to lower mononuclear phagocyte accumulation and is associated with higher brain Aβ levels, specifically around blood vessels, suggesting that monocytes accumulate at sites of Aβ deposition in an initial attempt to clear these deposits and stop or delay their neurotoxic effects. Indeed, enhancing mononuclear phagocyte accumulation delays progression of AD. Here we review the mechanisms of mononuclear phagocyte accumulation in AD and discuss the potential roles of additional chemokines and their receptors in this process. We also propose a multi-step model for recruitment of mononuclear phagocytes into the brain. The first step involves egress of monocyte/microglial precursors from the bone marrow into the blood. The second step is crossing the blood-brain barrier to the perivascular areas and into the brain parenchyma. The final step includes movement of monocytes/microglia from areas of the brain that lack any amyloid deposition to senile plaques. Understanding the mechanism of recruitment of mononuclear phagocytes to the AD brain is necessary to further understand the role of these cells in the pathogenesis of AD and to identify any potential therapeutic use of these cells for the treatment of this disease.
Keywords: Alzheimer' s disease